Proof: Slope 1
Let's prove the following theorem:
if the following are true:
- f = (a - b) / (c - d)
- a = w
- b = x
- c = y
- d = z
then f = (w - x) / (y - z)
Proof:
Given
1 | f = (a - b) / (c - d) |
---|---|
2 | a = w |
3 | b = x |
4 | c = y |
5 | d = z |
# | Claim | Reason |
---|---|---|
1 | (a - b) / (c - d) = (w - x) / (y - z) | if d = z and c = y and b = x and a = w, then (a - b) / (c - d) = (w - x) / (y - z) |
2 | f = (w - x) / (y - z) | if (a - b) / (c - d) = (w - x) / (y - z) and f = (a - b) / (c - d), then f = (w - x) / (y - z) |
Comments
Please log in to add comments